Effect of Profitability and Liquidity on Firm Value (Empirical Study On Food and Beverage Companies Listed On The Indonesia Stock Exchange) - Hertina, Dede; Wardani, Muhamad Erwin; Zilzalmi; Marampa, Adriana Madya (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to explain and determine the effect of Profitability and Liquidity on firm value jointly or partially and to determine the variables that have a dominant influence on firm value in food and beverage companies listed on the Indonesia Stock Exchange. Hypothesis testing used in this research is normality test, multicollinearity test, multiple linear regression test, and hypothesis testing which is divided into f test and t test. The results of the study stated that the profitability and liquidity variables had a positive effect but not too dominant because the hypothesis test was not accepted because it did not meet the minimum requirements for F and T tables. The F-count is smaller than the F-table value (0.923 < 4.76) and the significance value has a number > 0.05 (0.456 < 0.05.